Hubungan Perilaku Fear of Missing Out (FoMO) dengan Interaksi Sosial Siswa di Sekolah Menengah Atas Negeri 14 Pekanbaru (Tarbiyah Suska Conference Series, 2024)
This research was instigated by some students who were afraid of missing the moment or being left behind by trends, known as Fear of Missing Out (FoMO) behaviour. FoMO is known to influence the student social interaction quality level. This research was conducted to find out the description of FoMO behaviour, the description of students’ social interaction, and the correlation between students’ FoMO behaviour and their social interaction. Quantitative method was used in this research, and it was correlational descriptive. 1120 students at State Senior High School 14 Pekanbaru were the population of this research. The samples were 295 students determined with proportional stratified random sampling technique. The instruments used were FoMO and social interaction questionnaires with Likert scale model. The research data were analysed by using descriptive percentage and simple regression analysis. The research findings showed that the description of student FoMO behaviour was on quiet high category with the percentage 32.88%, the description of student social interaction was on quiet high category with the percentage 49.15%, and the correlation between students’ FoMO behaviour and their social interaction showed the correlation score -0.977 and the significance result 0.000 lower than 0.005. In the determination analysis, the result of R square was 0.809 or 80.9%, and R score was 0.900. These showed that there was a significant negative correlation between students’ FoMO behaviour and their social interaction. It meant that the lower students’ social interaction was, the higher their FoMO behaviour would be or vice versa. The research findings could be efforts in increasing student social interaction quality at school, so learning atmosphere could be better.
Keywords: Fear of Missing Out; Social Interaction